The importance of on-going maintenance in preserving the heritage listed buildings - M. A., A. Rahman; Akasah, Z. A.; Zuraidi, S. N. F. (Insight - Indonesian Society for Knowledge and Human Development, 2012)
— Maintenance is not only important in ensuring the condition and physical of the old building to operate safely and effectively, but it also for an activity that is important in determining the life long of the building, so that it can be preserve and be inherit by the next generation. The need of maintenance is not only on repairing but more towards prevention method. According to the previous study, maintenance is done reactively; this further will cost serious problems in future. Therefore maintenance need good planning from the early stage and is followed with on-going implementation from time to time by all those who are responsible in it. In conjunction with this, this paper is to discuss about the importance of on-going maintenance in order to manage the old building after it has been gazette as heritage listed. At the end of the discussion, several strategies have been put forward in order to stimulate the practice of on-going maintenance as an initiative to encourage the culture of maintenance and also help to increase the quality process in a more effective maintenance management